2018
DOI: 10.20945/2359-3997000000063
|View full text |Cite
|
Sign up to set email alerts
|

Hounsfield unit value has null effect on thyroid nodules at 18F-FDG PET/CT scans

Abstract: Objectives: Detection rate of thyroid nodules is increasing with the use of new imaging modalities, especially in screening for malignancies. Positron emission tomography/computed tomography (PET/ CT)-positive thyroid nodules should be differentiated for malignancy to avoid unnecessary operations and further follow-up. Most trials evaluate the role of SUV max , but there is no definitive information about the utility of Hounsfield unit (HU) values for prediction of malignancy. This study aimed to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Few studies have addressed the utilization of HU values on LDCT of F-18 FDG PET/CT for prediction of malignant TI [14,19,20,60,61]. In the current study, both benign and malignant lesions are relatively hypodense compared to normal thyroid gland density of control group.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Few studies have addressed the utilization of HU values on LDCT of F-18 FDG PET/CT for prediction of malignant TI [14,19,20,60,61]. In the current study, both benign and malignant lesions are relatively hypodense compared to normal thyroid gland density of control group.…”
Section: Discussionmentioning
confidence: 60%
“…Pérez et al [49] reported SUVmax 4.2 as the optimal threshold to discriminate malignancy with an area under receiver-operating characteristic curve of 0.76 (95 % confidence interval, 0.60-0.90). Haydardedeoglu et al [19] reported cut-off value for SUVmax to be 5.55. Some of previous publications reported a statistically significant difference between SUVmax of benign lesions and the value of malignant ones [4,14,[50][51][52][53], whereas other studies did not [5,18,32,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some research results showed that the benign and malignant TN had a reliable correlation with CT image characteristics [13,14]. Moreover, PET/CT was used in more and more studies to diagnose patients, and the semiquantitative index SUV max could be applied for the diagnosis and evaluation of benign and malignant nodules [15].…”
Section: Discussionmentioning
confidence: 99%